Prevalence of pulmonary tuberculosis among expatriates subjected to medical visa screening in Abu Dhabi, United Arab Emirates - Farida I. Al Hosani; Ghada A. Yahia (Springer, 2019)
Introduction: All applicants for work and/or residence in Abu Dhabi are screened for tuberculosis at the time of issuing or renewing their residence visa. The purpose of this study is to assess the prevalence of TB among visa applicants and the likelihood of testing positive among different subgroups. Methods: Data from the electronic visa screening system was used for a total of 948,504 applicants screened for residence in Abu Dhabi from January to December 2010. Results: The screening identified 4577 suspected cases of pulmonary tuberculosis (PTB); 1558 people with chest X-ray findings suggestive of prior PTB; 235 smear-positives; and 132 culture-positive cases. The prevalence of active PTB was 39/100,000, with new applicants significantly more likely to test positive compared with renewals (OR: 2.05, 95% CI: 1.5-2.7, P < .001). People coming from African countries had the highest prevalence of TB compared with people from other regions (OR: 21.25, 95% CI: 6.72-67.17, P < .001). Conclusion: The number of active PTB cases among applicants for visa screening is still of a real concern. Without a rigorous screening system, the disease can spread to the community and hit other people. Certain subgroups were more likely to have the disease; this could provide the scientific foundation for future amendments in the screening requirements.